Public Service Motivation, Public Management Reform, and Organizational Socialization: Testing the Effects of Employment At-Will and Agency on PSM Among Municipal Employees. (June 2016) - Battaglio, R. Paul; French, P. Edward
This study tests public service motivation (PSM) by accounting for organizational factors and socialization in shaping motives. Focusing on PSM and its four dimensions, we control for employment at-will as an organizational factor and agency type in influencing organizational socialization. Utilizing hierarchical linear modeling, we evaluate PSM in 10 municipalities at the individual level, while controlling for agency context as a predictor for a second level of analysis. The results underscore the effect of organizational factors, indicating that municipal employees in employment at-will environments have higher levels of self-sacrifice than their civil service counterparts. Although municipal employees in public safety agencies exhibit higher levels of self-sacrifice and commitment to the public interest than their peers in other agencies, their levels of attraction to policy making and compassion are significantly lower. The findings suggest the importance of a multi-dimensional approach to PSM when considering institutional factors and agency socialization in the workplace.